The rhetoric of main street media: an analysis of small-town newspapers - Shute, Austin T. (Kansas State University, 2022)
While traditional print media has long played a vital role in the circulation of political rhetoric, scant attention has been paid to minor market newspapers that service the populations of small rural towns. These papers, soon to be fully supplanted by electronic media, offer a unique window into the politics of rural communities, which during the Trump administration have been understood as the wellspring of virulent conservatism and populism. This project identifies and establishes newspapers published by Main Street Media as a unique and fertile archive for this sort of analysis. Main Street Media is the parent company of thirty-three newspapers that service small farm town markets in Kansas, Nebraska, and Missouri. To focus on the divisive political rhetoric surrounding crime, violence, and immigration, this project concentrates specifically on the opinion and politician statement sections of the three Main Street Media properties (Red Cloud Chief, Smith County Pioneer, and The Santa Fe Times) published in Nebraska, Kansas, and Missouri, respectively. With a sampling frame of January 2015 through January 2017, I capture both the end of the Obama presidency and the sequence of narratives leading into the Trump presidency. This strategy yields a sample of 729 unique opinion/political statement pieces. The aim of this project is to better understand the place of small-market newspapers as an ongoing site for the circulation of political rhetoric in the context of proliferating electronic, new media such as Facebook and Twitter, and to theorize editorial writers as key political actors in this milieu. The findings of this research show a significant use of the far-right populist narrative in these journalists’ responses to ongoing national and international cultural debate and support of politicians who adhere to this worldview. Implications for policy responses are also discussed.
Keywords: Far-right populism; Media; Rural